2016
DOI: 10.1007/s00018-016-2426-4
|View full text |Cite
|
Sign up to set email alerts
|

Enteric glial cells are susceptible to Clostridium difficile toxin B

Abstract: Clostridium difficile causes nosocomial/antibiotic-associated diarrhoea and pseudomembranous colitis. The major virulence factors are toxin A and toxin B (TcdB), which inactivate GTPases by monoglucosylation, leading to cytopathic (cytoskeleton alteration, cell rounding) and cytotoxic effects (cell-cycle arrest, apoptosis). C. difficile toxins breaching the intestinal epithelial barrier can act on underlying cells, enterocytes, colonocytes, and enteric neurons, as described in vitro and in vivo, but until now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
155
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(157 citation statements)
references
References 69 publications
2
155
0
Order By: Relevance
“…Since we observed previously that TcdB induced apoptosis in EGCs17, and confirmed here apoptosis already at 18-hour treatment (Supplementary Fig. S1), we investigated whether ROS act as an upstream signal in this process.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Since we observed previously that TcdB induced apoptosis in EGCs17, and confirmed here apoptosis already at 18-hour treatment (Supplementary Fig. S1), we investigated whether ROS act as an upstream signal in this process.…”
Section: Resultssupporting
confidence: 61%
“…JNK interacts with different pro- and anti-apoptotic proteins20 of Bcl-2 family members. We reported previously that TcdB did not induce changes in the expression/activation of Bax, Bak, Bcl-2, and Bcl-X L 17. One potential target of JNK is Bim.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In fact, TcB in vitro caused in a dose-and time-dependent manner cytopathic and cytotoxic effects on EGC, correlated with Rac1 glucosylation, such as cytoskeleton disorganization, cell-cycle arrest, apoptosis, increased susceptibility to apoptosis induced by proinflammatory cytokines [54]. More importantly, in EGC surviving the cytotoxic effect of TcdB persistently impaired cell functions were observed, such as Rac1 glucosylation and cell-cycle arrest, even though there was evidence of a selfrescuing mechanism as suggested by an increased production of glial-derived neurotrophic factor [54]. Moreover, surviving EGC were more susceptible to TNFα and IFNγ action, which induces apoptosis to doses of cytokines not affecting control EGC.…”
Section: Pi-ibs After C Difficile Infection: a Case Of A Microbiologmentioning
confidence: 97%
“…Recently, we reported that the adverse effects of toxin B extend to EGC [54]. In fact, TcB in vitro caused in a dose-and time-dependent manner cytopathic and cytotoxic effects on EGC, correlated with Rac1 glucosylation, such as cytoskeleton disorganization, cell-cycle arrest, apoptosis, increased susceptibility to apoptosis induced by proinflammatory cytokines [54].…”
Section: Pi-ibs After C Difficile Infection: a Case Of A Microbiologmentioning
confidence: 99%